Culture-Negative Peritonitis and the Latest Diagnostic Techniques - Jiajia Ye; Jing Sun; Dan Chen; Huanhuan Cao; Yi Lv; Chen Ye; Yumei Wang; Huajun Jiang (Kidney Diseases)
Background: Peritonitis is a common and serious complication of peritoneal dialysis that results in considerable morbidity, mortality, and increased healthcare costs. A positive culture-based microorganism test is one of the main criteria for the diagnosis of peritonitis. However, the rates of positive bacterial culture remain quite low. Summary: Peritonitis is a frequently encountered and consequential complication of peritoneal dialysis that poses a significant clinical burden in terms of morbidity, mortality, and healthcare expenditure. The reliance on culture-positive microbiological tests as a cornerstone of peritonitis diagnosis often results in a relatively low rate of positive results. Key Messages: This article aimed to present a comprehensive synthesis and critical analysis of the most recent diagnostic modalities used to identify peritonitis-associated pathogens in peritoneal dialysis. Emphasis was placed on both direct diagnostic tools for pathogen identification and rapid detection methodologies that facilitate expedited pathogen diagnosis in peritonitis.